EFL teachers’ and students’ beliefs about factors affecting students’ participation in group work activities at Hanoi National University of Education - Hoàng, Thị Minh (ĐHNN, 2017)
This survey research, based on the claim that EFL teachers and students highly valu e the application of group work and students’ participation in group work context, analyzed their beliefs about factors affecting students’ participation in group work activities and highlighted the importance of the conditions underlying effective classro om interaction. Quantitative and qualitative data gathered from survey questionnaires and interviews indicate both the similarity and difference in their beliefs. These teachers and students appreciated students’ preference to group work, appropriate group task, collaborative interaction; accepted the possibility to use native language ; and did not view fully prepar ing and knowing the right answer as a prerequisite for participation . However, while the learners believed that participation was impacted by is sues of students’ personality, group composition and teachers’ policy of grading participation ; the teachers’ beliefs were not so flexible . These results assert the significance of teachers’ and learners’ involvement in classroom research and draw attentio n to the need to incorporate learners’ beliefs into pedagogy.